2018
DOI: 10.7554/elife.33144
|View full text |Cite
|
Sign up to set email alerts
|

Network oscillation rules imposed by species-specific electrical coupling

Abstract: Electrical junctions are widespread within the mammalian CNS. Yet, their role in organizing neuronal ensemble activity remains incompletely understood. Here, in a functionally well-characterized system – neuroendocrine tuberoinfundibular dopamine (TIDA) neurons - we demonstrate a striking species difference in network behavior: rat TIDA cells discharge in highly stereotyped, robust, synchronized slow oscillations, whereas mouse oscillations are faster, flexible and show substantial cell-to-cell variability. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 57 publications
7
33
2
Order By: Relevance
“…This current is implicated in network rhythmicity (see (Luthi and McCormick, 1998), and contributes to depolarization of the resting membrane potential (Maccaferri et al, 1993); see (He et al, 2014), as observed in the lactating mothers (present results). Indeed, we have described a correlation between depolarization and oscillation frequency in mouse TIDA neurons, (Stagkourakis et al, 2018) and the present data show that pharmacological blockade of I h reduces the lactation-associated fast rhythm similar to the rate of nulliparous dams.…”
Section: Control Zd Control Zdsupporting
confidence: 75%
See 2 more Smart Citations
“…This current is implicated in network rhythmicity (see (Luthi and McCormick, 1998), and contributes to depolarization of the resting membrane potential (Maccaferri et al, 1993); see (He et al, 2014), as observed in the lactating mothers (present results). Indeed, we have described a correlation between depolarization and oscillation frequency in mouse TIDA neurons, (Stagkourakis et al, 2018) and the present data show that pharmacological blockade of I h reduces the lactation-associated fast rhythm similar to the rate of nulliparous dams.…”
Section: Control Zd Control Zdsupporting
confidence: 75%
“…Individual cells were marked as regions of interest (ROIs) from the image sequences i.e, all positive cells in one plane. Consistent with previous studies in mice, both oscillating and nonoscillating DAT-GCaMP3 cells were found (Stagkourakis et al, 2018;Zhang and van den Pol, 2015). Our focus in this study was on the oscillating population, which was selected by the fold difference in the intensity signal (≥ 1%) and the rhythmicity index (defined below; ≥ 0.2).…”
Section: Calcium Imagingsupporting
confidence: 55%
See 1 more Smart Citation
“…The expression of DAT in TIDA neurons is well documented (Meister and Elde, 1993;Revay et al, 1996;Demaria et al, 2000;Stagkourakis et al, 2018), yet the functional role of the transporter within the lactotropic axis remains controversial (Demarest and Moore, 1979;Annunziato et al, 1980;Meister and Elde, 1993;Revay et al, 1996;Bossé et al, 1997;Demaria et al, 2000;Stagkourakis et al, 2018). To assess whether reuptake is involved at determining dopamine levels at the entry to the portal vasculature, we performed optogenetic stimulation of TIDA terminals in the ME, in the absence and presence of the clinically prescribed DAT blocker, methylphenidate (Taylor and Ho, 1978;Volkow et al, 1999a, b).…”
Section: Functional Dat In the Mementioning
confidence: 99%
“…Dopamine, released in the median eminence (ME) for passage to the hypophyseal portal blood circulation, tonically inhibits the lactotropes through dopamine D2-type receptors (Gudelsky, 1981;Malgaroli et al, 1987;Israel et al, 1990;Lledo et al, 1990;Stefaneanu et al, 2000). Recent studies have revealed distinguishing electrophysiological characteristics of TIDA cells (Lyons et al, 2010), including the capacity for a variable repertoire of firing frequencies in mouse neurons (Romanò et al, 2013;Stagkourakis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%